Drivers of loyalty among non-Muslims towards Islamic banking in Malaysia evidence from SmartPLS - Mohd Thas Thaker, Hassanudin; Sakaran, K Chandra; Nanairan, N. Madhavan; Mohd Thas Thaker, Mohamed Asmy; Iqbal Hussain, Hafezali (Emerald Publishing Limited, 2020)
Purpose – The growth of Islamic banking seems to be tremendous and significant in the context of Malaysia. Moreover, together with Muslim loyalty towards Islamic banking, non-Muslims are also showing positive acceptance towards Islamic banking in Malaysia. Thus, this paper aims to examine the drivers of loyalty among non-Muslim in their adoption of Islamic banking products in Malaysia. Design/methodology/approach – The primary data are collected from the survey administered to non-Muslim clients in Kuala Lumpur and Selangor. The total number of respondents involved are n = 300. The analysis of data is conducted by using a partial least square analysis. Findings – This study documented that loyalty among non-Muslim Islamic banking customers in Malaysia was mainly driven by convenience, product pricing, reliability and responsiveness, operational risk and security and value added services. Only one variable was found to be insignificant, which was accessibility. Practical implications – The results from this research is expected to provide important inputs on the critical factors for consideration by Islamic banks in maintaining further loyalty among their non-Muslim customers, thus enhancing the development of Islamic banking in Malaysia. Originality/value – This paper provides further literature evidence on the factors contributes to loyalty by considering non-Muslims patronization of Islamic banking in Malaysia.